2007
DOI: 10.1161/hypertensionaha.107.098806
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor 2b Inhibition Provides Renal Protection in Angiotensin II–Salt Hypertension

Abstract: Abstract-The present study was designed to determine whether chemokine receptor 2b (CCR2b) contributes to the development of renal injury in salt-sensitive angiotensin II (ANG) hypertension. Rats were infused with ANG and fed a high-salt diet (HS) for 14 days. Rats were divided into 4 groups: HS; HS administered the CCR2b antagonist, RS102895; Ang/HS hypertensive; and Ang/HS hypertensive administered RS102895. CCR2b inhibition slowed the progression of blood pressure elevation during the first week of ANG/HS h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 38 publications
1
61
0
Order By: Relevance
“…However, it is important to recognize that impaired dynamic RBFA does not indicate a certain level of RBF at a certain level of AP, but more likely predicts whether the response of RBF following a dynamic change in arterial pressure will be normal. In line with our results, Elmarakby et al (13) showed that autoregulatory responses of afferent arterioles to step-wise increases in perfusion pressure were blunted in ANG II-infused rats on high dietary NaCl (13). However, in that study no comparison was made to ANG II-infused animals on a normal NaCl intake.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, it is important to recognize that impaired dynamic RBFA does not indicate a certain level of RBF at a certain level of AP, but more likely predicts whether the response of RBF following a dynamic change in arterial pressure will be normal. In line with our results, Elmarakby et al (13) showed that autoregulatory responses of afferent arterioles to step-wise increases in perfusion pressure were blunted in ANG II-infused rats on high dietary NaCl (13). However, in that study no comparison was made to ANG II-infused animals on a normal NaCl intake.…”
Section: Discussionsupporting
confidence: 90%
“…However, the pathophysiological mechanisms by which hypertension causes renal injury are multiple and incompletely understood (13,27,28,34). The results of the present study suggest that a very high-NaCl intake in ANG II-dependent forms of hypertension, in addition to elevating AP further, could increase the susceptibility to hypertensive glomerular injury by impairing RBFA.…”
Section: Perspectives and Significancementioning
confidence: 61%
See 2 more Smart Citations
“…3 There is accumulating evidence showing that inhibition of CCR2 attenuates renal injury in renal diseases. [4][5][6] These studies clearly indicate a role for CCR2 in the development of renal disease. The transient receptor potential vanilloid type 1 (TRPV1, also known as VR1) channel is originally found in primary sensory neurons that innervate various tissues including the heart, blood vessel, and kidney.…”
Section: Introductionmentioning
confidence: 69%